A Dual‐Functional Triboelectric Nanogenerator Based on the Comprehensive Integration and Synergetic Utilization of Triboelectrification, Electrostatic Induction, and Electrostatic Discharge to Achieve Alternating Current/Direct Current Convertible Outputs. Issue 7 (23rd December 2022) - Zeng, Qixuan; Chen, Ai; Zhang, Xiaofang; Luo, Yanlin; Tan, Liming; Wang, Xue
Abstract: Traditional alternating current (AC) and direct current (DC) triboelectric nanogenerators (TENGs), which are implemented via the pairwise coupling of triboelectrification, electrostatic induction, and electrostatic discharge, have been widely explored in various fields. In this work, the comprehensive integration and synergetic utilization of triboelectrification, electrostatic induction, and electrostatic discharge in a single device for the first time is realized, achieving a dual‐functional TENG (DF‐TENG) to produce an AC/DC convertible output. Distinguishing from the conventional TENGs, the coupling of triboelectrification and electrostatic discharge enables charge circulation between the dielectric tribo‐layers, while electrostatic induction realizes charge transfer in the external circuit. This novel energy conversion mechanism has been proven to be applicable to a variety of materials, including polymers, fabrics, and semiconductors. The output mode of the DF‐TENG can be tuned by adjusting the slider motion state, and its constant output current and power density can reach 1.51 mA m −2 Hz −1 and 398 mW m −2 Hz −1, respectively, which are the highest records reported for constant DC‐TENGs to date. This work not only provides a paradigm shift to achieve AC/DC convertible output, but it also exhibits high potential for extending the TENG design philosophy. Abstract : Through the comprehensive integration and synergetic utilization of triboelectrification, electrostatic induction, and electrostatic discharge, a brand‐new energy converter paradigm is achieved. The dual‐functional triboelectric nanogenerator can produce an alternating current/direct current convertible output by adjusting the slider motion state, generating a remarkable constant output current and power density of 1.51 mA m −2 Hz −1 and 398 mW m −2 Hz −1, respectively.